PENGARUH SPECIAL EVENT PL FAIR 2010 TERHADAP PENCITRAAN SMA PANGUDI LUHUR 1 JAKARTA - Rhamadhitya S.K, Heinrichus J (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
This study is to find out how special relationship PL Fair 2010 event with high image Pangudi Luhur 1 Jakarta, to know how special nature of the relationship between PL Fair 2010 event with high image Pangudi Luhur 1 Jakarta, and to find out how strong the influence of PL Fair 2010 special event the SMA image Pangudi Luhur 1 Jakarta. Location of the research conducted in the high school environment Pangudi 1 Luhur Jakarta. The population in this study is the first high school alumni Pangudi Luhur Jakarta class of 2007, amounting to as much as 90 and as many as 40 samples taken respondents. Variable in this study is the PL Fair 2010 special event as the independent variable and the image of SMA 1 Pangudi Luhur Jakarta so dependent variable. The results showed that there is significant influence between PL Fair 2010 special event with high image 1 Pangudi Luhur Jakarta.